Food Safety and Natural Toxins - Mary T. Fletcher; Gabriele Netzel (Toxins, 2020)
Natural toxins are poisonous secondary metabolites produced by living organisms, which are typically not harmful to the organisms themselves but can impact on human or animal health when consumed [...]